Future wind and wave energy resources and exploitability in the Mediterranean Sea by 2100. (15th November 2021) - Lira-Loarca, Andrea; Ferrari, Francesco; Mazzino, Andrea; Besio, Giovanni
Abstract: A state-of-the-art regional assessment of future wind and wave energy resource in the Mediterranean Sea and the projected changes with respect to hindcast is presented. A multi-model EURO-CORDEX ensemble of future wind field and wave climate conditions with a spatial resolution of ≈ 10–12.5 km and 3–6 h temporal resolution in the Mediterranean Sea is used for the assessment of future changes wind power, wave energy and combined exploitability under the climate change scenario RCP8.5. The results allow to identify climate change impacts in wind and wave power potential and the projected changes in the locations in the Mediterranean basin that were considered suitable for joint exploitations in previous studies. The future ES-Index allows to assess the optimized temporal-availability of combined wind and wave resources in a changing climate. Results show a robust decrease in the ES-Index during fall and winter in regions previously identified as suitable for coupled systems which would reduce the overall energy extraction but also attenuate the seasonal fluctuation. In addition, the Alboran Sea presents increases in ES-Index emerging as a probable suitable area for coupled systems under RCP8.5. Highlights: Wind and wave climate projections for the 21st century for a multimodel GCM–RCM ensemble are used. Projected changes in wind and wave energy resource for the Mediterranean Sea for mid-century and end-of-century are analyzed. Climate change impacts on the joint wind and wave energy exploitability are described. Future best combined blue energy exploitation areas are located.